Duplicate left gastric artery identified during laparoscopic distal gastrectomy. Issue 2 (1st September 2020) - Taki, Yusuke; Watanabe, Masaya; Sato, Shinsuke; Higashizono, Kazuya; Nagai, Erina; Nishida, Masato; Oba, Noriyuki
Abstract: The reported incidence of duplicate left gastric artery is not very low, with a rate of 0.4%. However, there have been no reports of the surgical management of patients with a duplicate left gastric artery. Here, we report a 60‐year‐old Japanese man diagnosed with clinical T1bN0M0 stage IA gastric cancer. Preoperative 5‐mm slice CT showed no anatomical abnormality, and the patient underwent laparoscopic distal gastrectomy. When we dissected the nerve plexus around the left gastric artery with an ultrasonic vessel‐sealing device, pulsating bleeding was observed from a small vessel in the nerve plexus. The bleeding was stopped by suture and clipping. A 1.2‐mm vessel was identified on 1‐mm slice preoperative CT and postoperative CT angiography. The patient was discharged without any complications. To the best of our knowledge, this is the first report of a patient undergoing surgery for a duplicate left gastric artery.